MEKANISME PERTAHANAN DIRI DI TENGAH BURNOUT DAN PEMICU SISTEMIK QUIET QUITTING: SEBUAH SYSTEMATIC LITERATURE REVIEW (SLR) - Wanda Novita; Fransisca Laij (Bisnis-Net, 2026)
This research conducts a systematic literature review of the quiet quitting phenomenon to map its intellectual evolution and systemic triggers within contemporary work dynamics. Using the PRISMA 2020 protocol, an analysis was conducted on 240 scientific documents from the Scopus database up to early 2026. Findings show an exponential explosion in publications since 2022, with a primary focus on the healthcare sector and human resource management. Descriptive analysis identifies that quiet quitting is not merely a social media trend, but rather a proactive coping mechanism against burnout and a manifestation of post-pandemic psychological contract renegotiation. This phenomenon is very prominent among Generation Z and healthcare workers, where limiting work effort is used as a mental health protection strategy. This research also highlights the emergence of quiet firing as a destructive managerial response. It is concluded that organizations must adopt empathic leadership and job designs that support mental resilience to mitigate the erosion of human capital. This study provides an important theoretical foundation for the development of employee retention strategies in the new normal era.